IDENTIFIKASI PERSIAPAN IMPLEMENTASI KAWASAN TANPA ROKOK (KTR) DI PROGRAM STUDI ILMU KEPERAWATAN DAN IMPLEMENTASI KTR DI FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Danti Arika Putri Nasution; Febriana " Sabrian; Darwin " Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstrak   The aim of this research is to identify the preparation for implementation of smoke free area policies in School of Nursing and the implementation smoke free area policies in Faculty of Medicine University of Riau. Research method is qualitative phenomenology. The participants in this research are 13 participants with 7 participants in School of Nursing and 6 participants in Faculty of Medicine. The participants were chosen with purposive sampling method and semistructure interview and systematic observation were employed to collect data. The data were analyzed by using  transcription, data organization, and analysis finding of interview. The result show that all participants agree that School of Nursing is ready  to implement smoke free area policies. Most participants believe that School of Nursing should be a role model for other helth-based schools. The process of implementation can be started from socialization, and need supporting facilities in implementation of smoke free area policies. In Faculty of Medicine, all participants know about regulation, benefits, and punishment of smoke free area policies. The enforcement of rules had little obstacle in the beginning, however Faculty of Medicine could overcame the problem. In addition, research finding suggests that Faculty of Medicine should prepare quit smooking facilities for smokers. However the participants were argue that smoking area is still needed in campus environment. It is suggested that the Dean of Faculty of Medicine to enforce 100% smoking free area in campus, and the Head of School of Nursing to begin the implementation of smoking free area in nursing campus. Keywords: Implementation, Preparation, Smoke-free area